Confirmatory factor analysis model of factors affecting the implementation of clinical guidelines in Iran - Kimiaeimehr, Farzaneh (Med J Islam Repub Iran, 2020)
Background: Clinical guidelines refer to a developed scientific statement to help physicians and patients for decision-making about the best care for special clinical conditions, which can be an important document to shape evidence-based medicine. This study aimed to identify factors affecting the implementation of clinical guidelines in Iran to enhance the quality of services. Methods: This descriptive analytical study was performed with combined quantitative-qualitative method in the first half of 2019. The statistical population consisted of 400 health managers and experts who were selected through multistage sampling method in 5 regions of Iran (north, south, center, east, and west). Overall, 20 academic experts were selected from each university. For data collection, a researcher-made questionnaire (n = 400) was used. To measure face and content validity, content validity ratio (CVR) and content validity index (CVI) were used. Also, to determine reliability, test-retest method, with Cronbach’s alpha coefficient of 0.934 was used. For data analysis, Lisrel 8.8 and SPSS 24 were used. Finally, fitness indices were used to determine the fitness of the model. Results: Six factors, including organizational (9 components), organizational culture (8 components), the clinical guidelines feature (8 components), insurance (7 components), and trusteeship of the health care system (8 components) were identified as the main dimensions. The economic dimension had the maximum effect on implementing clinical guidelines (0.90), while the clinical guidelines feature (0.63) and organizational culture (0.63) showed the minimum extent of effect on implementing clinical guidelines. Conclusion: Evidently, imposing the mentioned interventions with the ultimate goal of sustainable behavior change in providing health care services requires contribution of all practitioners, presentation of suitable facilities for implementing clinical guidelines based on evidence, time and personnel management, training methodology and planning, developing the necessary infrastructure, supervision, and developing professional and legal motivation.